Circles of deception: the Ebbinghaus illusion from fish to birds - Santacà, Maria; Quigley, Cliodhna; Fusani, Leonida (Frontiers in Psychology, 2025)
Understanding how animals perceive visual illusions provides valuable insights into the evolution of sensory systems and how these systems are adapted to meet the perceptual demands of an animal’s natural environment. This study investigates the susceptibility to the Ebbinghaus illusion in guppies (Poecilia reticulata) and ring doves (Streptopelia risoria), two species with contrasting ecological and sensory adaptations. The Ebbinghaus illusion, where the perceived size of a central circle is influenced by surrounding circles, offers a robust framework for exploring context-dependent size perception. Guppies displayed high susceptibility to the illusion, possibly reflecting their reliance on global visual processing for interpreting complex aquatic environments. This heightened sensitivity may reflect an adaptive response to dynamic light conditions and dense vegetation, where relative size cues facilitate tasks such as mate selection and foraging. Conversely, no consistent susceptibility to the illusion was found in ring doves, which may be attributed to their ecological adaptation as granivores, favoring local processing over global contextual integration. Such local-focused processing likely supports their need to visually discriminate discrete seeds within heterogeneous ground textures. However, high interindividual variability emerged in their responses, suggesting that factors such as past experiences or individual perceptual biases may play a role in shaping their perceptual strategies. These findings underscore the role of ecological pressures in shaping perceptual mechanisms and suggest how contrasting environmental demands can lead to diverse visual strategies even for the same illusion.